Optimizing extrusion pretreatment and big bluestem parameters for enzymatic hydrolysis to produce biofuel using response surface methodology - Chinnadurai, Karunanithy; Muthukumarappan, Kasiviswanathan (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Biomass has been identified as alternative renewable energy resource to replace 30% transportation fossil fuel through biofuels by 2.025. Big bluestem is a warm season native perennial grass warrants attention and studies revealed its potential as energy feedstock. Extrusion pretreatments employed on big bluestem showed a significant improvement on sugar recovery. The current study was undertaken to understand and optimize pretreatment conditions such as barrel temperature (45-225